2021
DOI: 10.3390/ijerph182412994
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Concentrations from Continuous Glucose Monitoring Devices Compared to Those from Blood Plasma during an Oral Glucose Tolerance Test in Healthy Young Adults

Abstract: Continuous glucose monitoring devices measure glucose in interstitial fluid. The devices are effective when used by patients with type 1 and 2 diabetes but are increasingly being used by researchers who are interested in the effects of various behaviours of glucose concentrations in healthy participants. Despite their more frequent application in this setting, the devices have not yet been validated for use under such conditions. A total of 124 healthy participants were recruited to a ten-day laboratory study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…CGM has proven beneficial in settings with frequent hypoglycemia by detecting a decreasing trend earlier than serum glucose checks. Another study found that CGM during an oral glucose tolerance test in healthy young adults was a possible alternative to sampling serum glucose concentrations [ 31 ]. Although many studies have applied CGM as a glucose-monitoring device outside the setting of diabetes, none have utilized the technology in stimulation tests where severe hypoglycemia is induced.…”
Section: Discussionmentioning
confidence: 99%
“…CGM has proven beneficial in settings with frequent hypoglycemia by detecting a decreasing trend earlier than serum glucose checks. Another study found that CGM during an oral glucose tolerance test in healthy young adults was a possible alternative to sampling serum glucose concentrations [ 31 ]. Although many studies have applied CGM as a glucose-monitoring device outside the setting of diabetes, none have utilized the technology in stimulation tests where severe hypoglycemia is induced.…”
Section: Discussionmentioning
confidence: 99%
“…Once the glucose data were aligned with the sleep-stage data, a 15 min delay was applied to the glucose data. This is because interstitial glucose concentrations appear up to 15 min later than they do in blood [33]. Sleep stages N2, N3, REM, and WASO were included in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The saliva samples for measuring cortisol were collected at 08:00 h, 08:30 h, and 08:45 h on baseline day 1 (BL), experimental days 2 (E2) and 5 (E5), and the recovery day (RC). The data presented here are part of a larger study examining the impact of time in bed on glucose tolerance [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%